The Effectiveness of the Flipped Classroom Learning Model on Improving Students' Critical Thinking Understanding at Taruna Vocational School Bandar Lampung - Septiana, Septiana; Syafei, Imam; Sunarto, Sunarto (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to examine the effectiveness of the Flipped Classroom learning model in enhancing students’ critical thinking skills in Islamic Religious Education at SMK Taruna Bandar Lampung. The research was motivated by the low levels of student engagement and critical thinking ability, largely due to the continued dominance of traditional teaching approaches. A quantitative approach was employed, using a quasi-experimental nonequivalent control group design. The sample consisted of 60 eleventh-grade students divided into two groups: an experimental group (Flipped Classroom) and a control group (conventional learning). The research instrument was a validated 20-item multiple-choice test. Data were analyzed using the Kolmogorov-Smirnov normality test, Levene's Test for homogeneity, independent sample t-test, N-Gain, and Cohen’s d effect size, assisted by SPSS 23.0 and Excel 2013. The results showed that the Flipped Classroom model was significantly more effective in improving critical thinking skills than the conventional method (p < 0.05), with an average N-Gain of 0.72 (high category) in the experimental group and a large effect size. These findings highlight the importance of student-centered, technology-based instructional innovations in strengthening critical thinking skills in Islamic Religious Education.